Catalytic oxidation catalyst as well as preparation method and application thereof
By regulating the pore size and distribution of the catalyst molecular sieve coating, quantitatively regulating the dispersion and active phase exposure of active metals, solving the problems of poor shape selection, low selectivity and poor activity of existing catalytic oxidation catalysts, and achieving efficient and economical catalytic oxidation effects.
Patent Information
- Application Number
- CN202311168704.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
When existing catalytic oxidation catalysts treat non-methane gases (such as CO, VOCs, etc.) in the exhaust gas discharged during chemical production, there are problems such as poor shape selection, low selectivity and poor activity, and the preparation cost is high and the process is complicated.
By regulating the pore size and distribution of the catalyst molecular sieve coating, the dispersion and active phase exposure of active metals are quantitatively regulated, the content of noble metal catalysts is reduced, the adsorption capacity of gas and oxygen is increased, and the catalytic efficiency is improved. The specific method includes using an acid-treated regular carrier, attaching a coating containing ZSM-5 molecular sieve, and dispersing precious metals and alloy metals in the coating.
The oxygen adsorption and activation capacity of the catalytic oxidation catalyst is improved, the catalytic oxidation efficiency is enhanced, the precious metal content is reduced, the operating cost is reduced, and the mechanical strength and raw material adaptability of the catalyst are improved.
Smart Images

Figure CN119588408A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and specifically to a catalytic oxidation catalyst and a preparation method and application thereof, and more specifically to a catalytic oxidation catalyst for removing non-methane gases such as CO and VOCs from exhaust gas and a preparation method thereof, as well as an application of removing non-methane gases (i.e., carbon-based oxygen-containing molecular gases, such as CO, VOCs, etc.) from exhaust gas by catalytic oxidation. Background Art
[0002] During the production and processing of petrochemicals, the exhaust gas produced contains non-methane gases such as CO and VOCs. For this type of exhaust gas, the recovery cost is relatively high. In order to meet the emission requirements, adsorption, photocatalysis, low-temperature plasma conversion, combustion and other methods are usually used to remove the non-methane gases. Among them, the catalytic oxidation method introduces a high-efficiency catalyst on the basis of the combustion method to reduce the temperature of the combustion process. It has the advantages of simple process and high removal efficiency, and therefore has received widespread attention. At present, the main treatment method for non-methane exhaust gas discharged from petrochemical plants is catalytic oxidation. The catalytic oxidation method can completely oxidize oxygen-containing small molecular gases to form carbon dioxide. At the same time, in order to meet the requirements of low pressure drop and large air volume conditions, the current catalytic oxidation method generally uses a monolithic catalyst loaded with precious metals. However, the pore distribution of the coating is uneven and cannot be controlled, resulting in poor shape selectivity of the catalyst, low selectivity, and poor activity.
[0003] Patent application CN102689911A uses microwave alkali treatment to corrode nano-scale ZSM-5 molecular sieves to prepare multi-level pore ZSM-5 molecular sieve nanospheres with adjustable pore size between 30-150nm. However, these preparation methods of multi-level pore molecular sieves have the problems of high preparation cost and complicated process, which is not conducive to large-scale production.
[0004] Patent application CN107720771A discloses a method for preparing a macroporous-microporous molecular sieve catalyst TS-1, which uses mesoporous silica microspheres as hard templates and silicon sources, and controls the reaction temperature, reaction time, and the amount of structure-directing agent to synthesize a macroporous-microporous molecular sieve catalyst with adjustable macropore diameter. However, the preparation of the molecular sieve only introduces the macropore diameter, and does not achieve adjustable diameter, making it difficult to flexibly adapt to the ever-changing raw material requirements.
[0005] Patent application CN111408342A discloses a high-silicon composite molecular sieve adsorbent for VOCs removal and its preparation method. This method performs hydrothermal crystallization under microwave conditions, regulates the surface hydrophobicity of the molecular sieve pores, but does not change the pore structure and size, and cannot fully utilize its shape-selective catalytic ability.
[0006] Therefore, the development of catalysts with adjustable pores, high efficiency, low cost, environmental friendliness, and long-lasting strength has become a research hotspot and application trend of catalytic oxidation catalysts at home and abroad. Summary of the invention
[0007] The purpose of the present invention is to provide a catalytic oxidation catalyst and its preparation method and application for an efficient removal process of non-methane gases (such as CO, VOCs, etc.) in tail gas discharged from a chemical production process. The present invention regulates the pore size and pore distribution of the catalyst molecular sieve coating, quantitatively regulates the dispersion of active metals and the exposure of active phases, efficiently constructs catalytic active sites on the catalyst surface, reduces the content of precious metal catalysts, increases the adsorption capacity of CO, VOCs gases and oxygen, promotes the adsorption and activation of oxygen, and thus improves the catalytic efficiency of the catalyst.
[0008] In order to achieve the above object, the present invention provides a catalytic oxidation catalyst on one hand, the catalytic oxidation catalyst comprising:
[0009] A carrier, wherein the carrier is a regular carrier treated with acid;
[0010] a coating layer attached to the support, the coating layer comprising a ZSM-5 molecular sieve and optionally a metal oxide; and
[0011] an active component dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal;
[0012] The particle size of the coating is 50-500nm, the mesopore size is 3-50nm, and the specific surface area is 300-600m 2 / g, and the particle size of the active component is 1-8nm.
[0013] Preferably, the coating has a particle size of 80-300 nm, a mesopore size of 4-30 nm, and a specific surface area of 350-500 m 2 / g, and the particle size of the active component is 2-6nm.
[0014] Preferably, the powder loss rate of the coating is less than 1%, preferably 0.1-1%.
[0015] Preferably, relative to 100 parts by weight of the carrier, the content of the coating layer is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight.
[0016] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0017] Preferably, in the coating, the weight ratio of the ZSM-5 molecular sieve to the metal oxide is 1:0.1-0.5.
[0018] Preferably, in the coating, the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0019] Preferably, in the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3.
[0020] Preferably, the noble metal is selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium.
[0021] Preferably, the alloy metal is at least one of Fe, La and Ce, and preferably a combination of Fe, La and Ce.
[0022] A second aspect of the present invention provides a method for preparing a catalytic oxidation catalyst, the method comprising the following steps:
[0023] (1) treating the structured support with acid;
[0024] (2) mixing an alcohol solution of sodium metaaluminate with an aqueous solution containing a microporous template and a silicon source, aging, removing alcohol, and then mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and a mesoporous template;
[0025] (3) mixing the mixed solution obtained in step (2) with the metal oxide and ball milling to obtain a coating slurry;
[0026] (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and a structural additive, and the obtained mixed slurry is added to the structured support treated with acid, and then purged, dried, calcined and reduced in sequence.
[0027] Preferably, in step (1), the acid treatment process comprises: subjecting the structured carrier to a reflux treatment with an acidic solution, and then washing it to neutrality and drying it.
[0028] Preferably, the concentration of the acidic solution is 1-3 mol / L.
[0029] Preferably, the acid in the acidic solution is at least one of nitric acid, sulfuric acid and hydrochloric acid.
[0030] Preferably, the reflux treatment conditions include: a temperature of 70-90° C. and a time of 12-36 hours.
[0031] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0032] Preferably, in step (2), the specific process of mixing the alcohol solution of sodium aluminate with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of sodium aluminate to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours.
[0033] Preferably, the microporous template agent is selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide.
[0034] Preferably, the silicon source is selected from at least one of silicates, silicic acid, silica hydrogel and tetraethyl orthosilicate.
[0035] Preferably, the concentration of the mesoporous template agent is 0.5-5 mol / L, preferably 1-3 mol / L.
[0036] Preferably, the mesoporous template agent is cetyltrimethylammonium bromide (CTAB).
[0037] Preferably, in step (3), the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0038] Preferably, in step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12.
[0039] Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, 2-hydroxyethylamine hexahydroxoplatinic acid (IV), platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0040] Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0041] Preferably, in step (4), the purging process is performed by using an air knife purging at 1.5-2.5 MPa.
[0042] Preferably, the calcination conditions include: a temperature of 200-300° C. and a time of 4-10 hours.
[0043] Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations.
[0044] Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
[0045] The third aspect of the present invention provides a catalytic oxidation catalyst prepared by the above method.
[0046] The third aspect of the present invention provides the use of the above-mentioned catalytic oxidation catalyst in removing carbon-based oxygen-containing molecular gases from exhaust gas.
[0047] According to the technical scheme of the present invention, in the preparation process of the catalyst, the structured carrier is treated with acid and then a coating slurry containing ZSM-5 molecular sieve is attached. The ZSM-5 molecular sieve in the coating slurry can react with the exposed hydroxyl groups on the surface of the structured carrier after the acid treatment, and a chemical bond is formed between the coating and the structured carrier, so that the coating has high firmness and extremely low powder loss rate; and, in the technical scheme of the present invention, the concentration of the mesoporous template can be adjusted to control the mesoporous channel size and distribution of the coating matrix, thereby achieving the control of the coating structure of the catalytic oxidation catalyst, promoting the dispersion of active precious metals and the exposure of active phases, efficiently constructing catalytic active sites on the catalyst surface, reducing the content of precious metal catalysts, and increasing the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen, promoting the adsorption and activation of oxygen, and thereby improving the catalytic efficiency of the catalyst.
[0048] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0049] (1) Compared with other catalytic oxidation catalysts, the catalytic oxidation catalyst of the present invention has higher oxygen adsorption and activation capabilities and higher catalytic oxidation efficiency;
[0050] (2) Compared with other catalytic oxidation catalysts, the catalytic oxidation catalyst of the present invention has greater mechanical strength and is suitable for high space velocity and large volume gas treatment conditions;
[0051] (3) Compared with other catalytic oxidation catalysts, the catalytic oxidation catalyst of the present invention has the advantages of adjustable coating matrix pore structure, strong quantitative adjustability, strong raw material adaptability, etc.;
[0052] (4) Compared with other catalytic oxidation catalysts, the catalytic oxidation catalyst of the present invention has a low precious metal content, which can greatly reduce operating costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is the nitrogen adsorption-desorption curve of the pores of the coating particles in the catalytic oxidation catalyst prepared in Example 1;
[0054] Figure 2This is a TEM image of the coating particles in the catalytic oxidation catalyst prepared in Example 1. DETAILED DESCRIPTION
[0055] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0056] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0057] In the present invention, unless otherwise specified, the concentration "%" of a gas refers to "volume %"; the "space velocity" refers to "volume space velocity"; and the pressure refers to absolute pressure.
[0058] The catalytic oxidation catalyst of the present invention comprises:
[0059] A carrier, wherein the carrier is a regular carrier treated with acid;
[0060] a coating layer attached to the support, the coating layer comprising a ZSM-5 molecular sieve and optionally a metal oxide; and
[0061] An active component is dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal.
[0062] In the catalytic oxidation catalyst of the present invention, the ZSM-5 molecular sieve in the coating has a strong bonding strength with the acid-treated regular carrier, and the powder loss rate of the coating is low. Specifically, the powder loss rate of the coating is less than 1%, preferably 0.1-1%, and more preferably 0.1-0.5%. In the present invention, the powder loss rate is detected by ultrasonic oscillation method, and the detection conditions include: ultrasonic frequency 45kHz, ultrasonic power 130W, and treatment time 60min.
[0063] In the catalytic oxidation catalyst of the present invention, the particle size of the coating layer may be 50-500 nm, preferably 80-300 nm, and more preferably 80-150 nm.
[0064] In the catalytic oxidation catalyst of the present invention, the mesopore size of the coating can be adjusted. Specifically, the mesopore size and distribution of the coating can be regulated by adjusting the concentration of the mesoporous template during the preparation process. Specifically, the mesopore size of the coating can be in the range of 3-50 nm, preferably 4-30 nm.
[0065] In the catalytic oxidation catalyst of the present invention, the specific surface area of the coating can be 300-600m 2 / g, preferably 350-500m 2 / g.
[0066] In the catalytic oxidation catalyst of the present invention, the active component is fully dispersed in the coating layer, and the particle size of the active component is relatively small. Specifically, the particle size of the active component is 1-8 nm, preferably 2-6 nm.
[0067] In the catalytic oxidation catalyst described in the present invention, relative to 100 parts by weight of the carrier, the content of the coating layer can be 1-10 parts by weight, specifically, for example, it can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight; the content of the active component can be 0.1-1 part by weight, specifically, for example, it can be 0.1 part by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight or 1 part by weight; the content of the active component can be 0.1-1 part by weight, specifically, for example, it can be 0.1 part by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight or 1 part by weight.
[0068] In the catalytic oxidation catalyst described in the present invention, the regular carrier can be selected from at least one of cordierite honeycomb carrier, mullite honeycomb carrier, diamond honeycomb carrier, corundum honeycomb carrier, zirconium corundum honeycomb carrier, quartz honeycomb carrier, nepheline honeycomb carrier, feldspar honeycomb carrier and alumina honeycomb carrier, and the most preferred one is cordierite honeycomb carrier.
[0069] In the catalytic oxidation catalyst of the present invention, in the coating, the metal oxide is an optional component. In a more preferred embodiment, the coating contains ZSM-5 molecular sieve and metal oxide. When the coating contains metal oxide, the weight ratio of the ZSM-5 molecular sieve to the metal oxide can be 1:0.1-0.5, preferably 1:0.2-0.4.
[0070] In the catalytic oxidation catalyst of the present invention, in the coating layer, the metal oxide may be selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0071] In the catalytic oxidation catalyst of the present invention, in the active component, the alloy metal is an optional component. In a more preferred embodiment, the active component contains a noble metal and an alloy metal. In this preferred embodiment, the active component exists in the form of a noble metal element, an alloy, and a noble metal oxide. In the active component, the molar ratio of the noble metal to the alloy metal can be 1:0.1-0.3, preferably 1:0.15-0.2.
[0072] In the catalytic oxidation catalyst of the present invention, in the active component, the noble metal can be selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. When the noble metal is a combination of platinum and palladium, the molar ratio of platinum to palladium can be 1:0.5-2, and most preferably 1:1.
[0073] In the catalytic oxidation catalyst of the present invention, in the active component, the alloy metal may be at least one of Fe, La and Ce, preferably a combination of Fe, La and Ce. When the alloy metal is a combination of Fe, La and Ce, the molar ratio of Fe, La and Ce may be 1:0.5-2:0.5-2, most preferably 1:1:1.
[0074] According to some embodiments of the present invention, the catalytic oxidation catalyst comprises:
[0075] A carrier, wherein the carrier is a regular carrier treated with acid;
[0076] A coating attached to the carrier, wherein the coating is a ZSM-5 molecular sieve; and
[0077] An active component dispersed in the coating, wherein the metal in the active component is a noble metal;
[0078] The particle size of the coating is 50-500nm, the mesopore size is 3-50nm, and the specific surface area is 300-600m 2 / g, the particle size of the active component is 1-8nm, and the powder loss rate of the coating is less than 1%; relative to 100 parts by weight of the carrier, the content of the coating is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight;
[0079] The structured carrier is selected from at least one of cordierite honeycomb carrier, mullite honeycomb carrier, diamond honeycomb carrier, corundum honeycomb carrier, zirconium corundum honeycomb carrier, quartz honeycomb carrier, nepheline honeycomb carrier, feldspar honeycomb carrier and alumina honeycomb carrier; the precious metal is selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum.
[0080] According to some other embodiments of the present invention, the catalytic oxidation catalyst comprises:
[0081] A carrier, wherein the carrier is a regular carrier treated with acid;
[0082] A coating layer attached to the carrier, wherein the coating layer is a ZSM-5 molecular sieve and a metal oxide; and
[0083] An active component dispersed in the coating, wherein the metal in the active component is a noble metal or an alloy metal;
[0084] The particle size of the coating is 50-500nm, the mesopore size is 3-50nm, and the specific surface area is 300-600m 2 / g, the particle size of the active component is 1-8nm, and the powder loss rate of the coating is less than 1%; relative to 100 parts by weight of the carrier, the content of the coating is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight;
[0085] The structured carrier is selected from at least one of cordierite honeycomb carrier, mullite honeycomb carrier, diamond honeycomb carrier, corundum honeycomb carrier, zirconium corundum honeycomb carrier, quartz honeycomb carrier, nepheline honeycomb carrier, feldspar honeycomb carrier and alumina honeycomb carrier; the precious metal is selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum; the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2; the alloy metal is at least one of Fe, La and Ce.
[0086] According to some other embodiments of the present invention, the catalytic oxidation catalyst comprises:
[0087] A carrier, wherein the carrier is a regular carrier treated with acid;
[0088] A coating layer attached to the carrier, wherein the coating layer is a ZSM-5 molecular sieve and a metal oxide; and
[0089] An active component dispersed in the coating, wherein the metal in the active component is a noble metal or an alloy metal;
[0090] The particle size of the coating is 80-300nm, the mesopore size is 4-30nm, and the specific surface area is 350-500m 2 / g, the particle size of the active component is 2-6nm, and the powder loss rate of the coating is 0.1-1%; relative to 100 parts by weight of the carrier, the content of the coating is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight;
[0091] The structured carrier is selected from at least one of cordierite honeycomb carrier, mullite honeycomb carrier, diamond honeycomb carrier, corundum honeycomb carrier, zirconium corundum honeycomb carrier, quartz honeycomb carrier, nepheline honeycomb carrier, feldspar honeycomb carrier and alumina honeycomb carrier; the precious metal is a combination of platinum and palladium; the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2; the alloy metal is a combination of Fe, La and Ce.
[0092] According to some other embodiments of the present invention, the catalytic oxidation catalyst comprises:
[0093] A carrier, wherein the carrier is a regular carrier treated with acid;
[0094] A coating attached to the carrier, wherein the coating is a ZSM-5 molecular sieve and a metal oxide, and the weight ratio of the ZSM-5 molecular sieve to the metal oxide is 1:0.1-0.5; and an active component dispersed in the coating, wherein the metal in the active component is a noble metal and an alloy metal, and the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3;
[0095] The particle size of the coating is 80-300nm, the mesopore size is 4-30nm, and the specific surface area is 350-500m 2 / g, the particle size of the active component is 2-6nm, and the powder loss rate of the coating is 0.1-1%; relative to 100 parts by weight of the carrier, the content of the coating is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight;
[0096] The structured carrier is selected from at least one of cordierite honeycomb carrier, mullite honeycomb carrier, diamond honeycomb carrier, corundum honeycomb carrier, zirconium corundum honeycomb carrier, quartz honeycomb carrier, nepheline honeycomb carrier, feldspar honeycomb carrier and alumina honeycomb carrier; the precious metal is a combination of platinum and palladium, and the molar ratio of platinum to palladium can be 1:0.5-2; the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2; the alloy metal is a combination of Fe, La and Ce, and the molar ratio of Fe, La and Ce can be 1:0.5-2:0.5-2.
[0097] The method for preparing the catalytic oxidation catalyst of the present invention comprises the following steps:
[0098] (1) treating the structured support with acid;
[0099] (2) mixing an alcohol solution of sodium metaaluminate with an aqueous solution containing a microporous template and a silicon source, aging, removing alcohol, and then mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and a mesoporous template;
[0100] (3) mixing the mixed solution obtained in step (2) with the metal oxide and ball milling to obtain a coating slurry;
[0101] (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and a structural additive, and the obtained mixed slurry is added to the structured support treated with acid, and then purged, dried, calcined and reduced in sequence.
[0102] In step (1), the acid treatment process can remove impurities contained in the structured support and form a bare hydroxyl surface. The acid treatment process can include: refluxing the structured support with an acidic solution, then washing to neutrality and drying.
[0103] Specifically, the concentration of the acidic solution may be 1-3 mol / L, preferably 1.5-2.5 mol / L, and most preferably 2 mol / L.
[0104] Specifically, the acid in the acidic solution may be an inorganic strong acid, preferably at least one of nitric acid, sulfuric acid and hydrochloric acid, and most preferably nitric acid.
[0105] Specifically, the reflux treatment conditions may include: a temperature of 70-90° C., preferably 80° C.; and a time of 12-36 hours, preferably 24 hours.
[0106] In the method described in the present invention, the regular carrier can be selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, preferably a cordierite honeycomb carrier.
[0107] In step (2), the specific process of mixing the alcohol solution of sodium aluminate with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of sodium aluminate to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours.
[0108] In the present invention, in the alcohol solution of sodium aluminate, the alcohol solvent used may be at least one of isopropanol, ethanol and n-propanol.
[0109] In the present invention, the concentration of the alcohol solution of sodium metaaluminate may be 5-15% by weight.
[0110] In the present invention, the silicon source can be selected from water-soluble or water-soluble silicon-containing compounds, generally referring to a silicon dioxide (SiO2) source. In a specific embodiment, the silicon source includes but is not limited to at least one of silicate, silicic acid, silica hydrogel and tetraethyl orthosilicate, preferably tetraethyl orthosilicate.
[0111] In the present invention, the microporous template agent may be at least one selected from tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide.
[0112] In the method of the present invention, the mesopore size and distribution of the coating layer of the prepared catalytic oxidation catalyst can be regulated by adjusting the concentration of the mesoporous template agent. Specifically, the concentration of the mesoporous template agent can be adjusted in the range of 0.5-5 mol / L (preferably 1-3 mol / L), so that the mesopore channel size of the coating layer of the prepared catalytic oxidation catalyst can be regulated in the range of 3-50 nm (preferably 4-30 nm).
[0113] In the present invention, the mesoporous template agent may be a conventional template agent in the art. In a preferred embodiment, the mesoporous template agent is hexadecyltrimethylammonium bromide (CTAB).
[0114] In step (2), the aging process can be carried out at room temperature for 2-5 hours.
[0115] In step (2), the alcohol removal process is specifically as follows: heating the aged mixed solution to 85-95°C at a rate of 1-20°C / min (preferably 5-17°C / min), and removing alcohol at 85-95°C for 10-15 hours.
[0116] In step (2), the process of mixing the gel solution with the ZSM-5 molecular sieve seed crystals and the mesoporous template agent is carried out under stirring. The mixing conditions may include: a temperature of 35-45° C. and a time of 0.5-2 hours.
[0117] In the present invention, the metal oxide may be selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
[0118] In step (3), the mixing ball milling time can be 1-5 hours, preferably 2-3 hours.
[0119] In step (4), the coating slurry is mixed with a mixed solution containing a noble metal precursor and a structural additive under stirring. The mixing conditions may include: a temperature of 15-40° C., preferably 25° C.; and a time of 1-4 hours, preferably 3 hours.
[0120] In step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12. Specifically, the pH value of the mixed solution can be 9, 10, 11 or 12, for example.
[0121] In the present invention, the noble metal in the noble metal precursor is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. In a specific embodiment, the noble metal precursor is at least one of chloroplatinic acid, hexahydrooxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0122] In step (4), the structural additive is added to form an alloy with the noble metal. In a specific embodiment, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0123] In step (4), the purging process may be performed by using an air knife purging at 1.5-2.5 MPa.
[0124] In step (4), the drying process can be carried out in a drying oven. Specifically, the temperature of the drying oven can be 80-120° C., preferably 100° C.; the drying time can be 5-24 hours, preferably 12 hours.
[0125] In step (4), the calcination conditions may include: a temperature of 200-300° C. and a time of 4-10 hours.
[0126] In step (4), during the reduction process, the reducing atmosphere may be H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations. In a specific embodiment, the reducing atmosphere is a mixed atmosphere of different H2 concentrations and / or a mixed atmosphere of different CO concentrations, and the formation of surface oxygen vacancies of the catalyst is efficiently controlled by regulating the reducing atmosphere. Specifically, the reducing atmosphere may be, for example, 5% H2 (N2 dilution), 10% H2 (N2 dilution), 15% H2 (N2 dilution), 5% CO (N2 dilution), etc.
[0127] In step (4), the reduction conditions may include: a catalyst heating rate of 2-20° C. / min, a reduction temperature of 300-450° C., and a reduction time of 1-10 h.
[0128] In the method described in the present invention, the amounts of various reaction raw materials used in steps (1) to (4) are such that in the prepared catalytic oxidation catalyst, the content of the coating is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight relative to 100 parts by weight of the carrier.
[0129] According to some embodiments of the present invention, the method for preparing the catalytic oxidation catalyst comprises the following steps:
[0130] (1) refluxing the structured support with an acidic solution, then washing it to neutrality and drying it to obtain an acid-treated structured support;
[0131] (2) adding an alcohol solution of sodium metaaluminate to an aqueous solution containing a microporous template and a silicon source at a rate of 0.005-0.015 mL / min, stirring and mixing for 2-5 hours, aging, removing alcohol, and then mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and a mesoporous template to obtain a mixed solution;
[0132] (3) mixing the mixed solution with a metal oxide and ball milling to obtain a coating slurry;
[0133] (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and a structural additive, and the obtained mixed slurry is added to the acid-treated structured support, and purged with a 1.5-2.5 MPa air knife, followed by drying, calcining and reducing in sequence.
[0134] According to other embodiments of the present invention, the method for preparing the catalytic oxidation catalyst comprises the following steps:
[0135] (1) refluxing the structured support with an acidic solution, then washing it to neutrality and drying it to obtain an acid-treated structured support;
[0136] (2) adding an alcohol solution of sodium aluminate to an aqueous solution containing a microporous template and a silicon source at a rate of 0.005-0.015 mL / min, stirring and mixing for 2-5 hours, aging, removing alcohol, and then mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and a mesoporous template to obtain a mixed solution, wherein the concentration of the alcohol solution of sodium aluminate is 5-15% by weight, the mesoporous template is CTAB, and the concentration of the mesoporous template is in the range of 0.5-5 mol / L;
[0137] (3) mixing the mixed solution with a metal oxide and ball milling to obtain a coating slurry;
[0138] (4) Mixing the coating slurry with a mixed solution containing a noble metal precursor and a structural additive, adding the obtained mixed slurry to the acid-treated regular carrier, blowing with a 1.5-2.5 MPa air knife, and then drying, calcining and reducing in sequence, wherein the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12, the noble metal in the noble metal precursor is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, and the metal in the structural additive is at least one of Fe, La and Ce; the calcining conditions include: a temperature of 200-300°C and a time of 4-10 hours; the reducing atmosphere of the reduction process is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations; the reduction conditions include: a catalyst heating rate of 2-20°C / min, a reduction temperature of 300-450°C, and a reduction time of 1-10h.
[0139] According to other embodiments of the present invention, the method for preparing the catalytic oxidation catalyst comprises the following steps:
[0140] (1) using an acidic solution to reflux the structured support, then washing it to neutrality and drying it to obtain an acid-treated structured support, wherein the concentration of the acidic solution is 1-3 mol / L, the acid used is at least one of nitric acid, sulfuric acid and hydrochloric acid, and the structured support is selected from at least one of a cordierite honeycomb support, a mullite honeycomb support, a diamond honeycomb support, a corundum honeycomb support, a zirconium corundum honeycomb support, a quartz honeycomb support, a nepheline honeycomb support, a feldspar honeycomb support and an alumina honeycomb support;
[0141] (2) adding an alcohol solution of sodium aluminate to an aqueous solution containing a microporous template and a silicon source at a rate of 0.005-0.015 mL / min, stirring and mixing for 2-5 hours, aging at room temperature for 2-5 hours, heating the aged mixed solution to 85-95° C. at a rate of 1-20° C. / min, removing alcohol at 85-95° C. for 10-15 hours, and then mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and a mesoporous template to obtain a mixed solution, wherein the concentration of the alcohol solution of sodium aluminate is 5-15% by weight, the mesoporous template is CTAB, and the concentration of the mesoporous template is in the range of 0.5-5 mol / L;
[0142] (3) mixing the mixed solution with a metal oxide and ball milling to obtain a coating slurry, wherein the metal oxide is at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2;
[0143] (4) Mixing the coating slurry with a mixed solution containing a noble metal precursor and a structural additive, adding the obtained mixed slurry to the acid-treated regular carrier, blowing with a 1.5-2.5 MPa air knife, and then drying, calcining and reducing in sequence, wherein the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12, the noble metal in the noble metal precursor is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, and the metal in the structural additive is at least one of Fe, La and Ce; the calcining conditions include: a temperature of 200-300°C and a time of 4-10 hours; the reducing atmosphere of the reduction process is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations; the reduction conditions include: a catalyst heating rate of 2-20°C / min, a reduction temperature of 300-450°C, and a reduction time of 1-10h.
[0144] According to other embodiments of the present invention, the method for preparing the catalytic oxidation catalyst comprises the following steps:
[0145] (1) using an acidic solution to reflux the structured carrier, then washing it to neutrality and drying it to obtain an acid-treated structured carrier, wherein the reflux treatment conditions include: a temperature of 70-90° C. and a time of 12-36 hours; a concentration of the acidic solution of 1.5-2.5 mol / L, the acid used is nitric acid, and the structured carrier is a cordierite honeycomb carrier;
[0146] (2) adding an alcohol solution of sodium metaaluminate having a concentration of 5-15 wt % to an aqueous solution containing a microporous template and a silicon source at a rate of 0.005-0.015 mL / min, stirring and mixing for 2-5 hours, aging at room temperature for 2-5 hours, heating the aged mixed solution to 85-95° C. at a rate of 1-20° C. / min, removing alcohol at 85-95° C. for 10-15 hours, and then stirring and mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and CTAB to obtain a mixed solution, wherein the concentration of CTAB used is in the range of 0.5-5 mol / L;
[0147] (3) mixing the mixed solution with a metal oxide and ball milling to obtain a coating slurry, wherein the metal oxide is at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2;
[0148] (4) mixing the coating slurry with a mixed solution containing a noble metal precursor and a structural additive under stirring at 15-40° C. for 1-4 hours, adding the obtained mixed slurry dropwise to the acid-treated regular carrier, blowing with a 1.5-2.5 MPa air knife, and then drying, roasting and reducing in sequence, wherein the pH value of the mixed solution containing a noble metal precursor and a structural additive is 9-12, and the noble metal precursor is a platinum precursor (such as chloroplatinic acid, hexahydroplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate , acetylacetonate platinum, etc.) and a palladium precursor (such as palladium chloride, palladium nitrate, palladium acetate, etc.), the structural additives are ferric nitrate, cerium nitrate and lanthanum nitrate; the calcination conditions include: a temperature of 200-300°C and a time of 4-10 hours; the reducing atmosphere of the reduction process is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations; the reduction conditions include: a catalyst heating rate of 2-20°C / min, a reduction temperature of 300-450°C, and a reduction time of 1-10h.
[0149] The present invention also provides a catalytic oxidation catalyst prepared by the above method. In the catalytic oxidation catalyst, the ZSM-5 molecular sieve in the coating reacts with the exposed hydroxyl groups on the surface of the regular carrier treated with acid to form a chemical bond, so that the coating has high firmness and extremely low powder loss rate; moreover, the active precious metal is evenly dispersed and the particle size of the active component is small.
[0150] The present invention also provides the use of the catalytic oxidation catalyst in removing carbon-based oxygen-containing molecular gases from exhaust gas.
[0151] The catalytic oxidation catalyst and its preparation method and application of the present invention are further illustrated by examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0152] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0153] Example 1
[0154] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0155] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 14mL of CTAB (1mol / L) at 40°C for 1h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0156] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-1. The content of active components is 0.1% by weight, the particle size of active components is between 3-4nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 4.1-5.5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.1%.
[0157] The nitrogen adsorption-desorption curve and TEM image of the pores of the coating particles in the catalytic oxidation catalyst are shown in Figure 2. Figure 1 and Figure 2 As shown in the figure, it can be seen that the pores of the monolithic catalyst coating particles are a multi-level pore structure, and the interior of the pores is a spherical cavity structure.
[0158] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1, reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0159] Example 2
[0160] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0161] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 1g of commercially available ZSM-5 seeds and 14mL of CTAB (2mol / L) at 40°C for 1h to obtain solution 5, and 0.35g of metal oxide Al2O3 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0162] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-2. The content of active components is 0.1% by weight, the particle size of active components is between 3-4nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 6-9.5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.2%.
[0163] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0164] Example 3
[0165] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0166] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 10g of commercially available ZSM-5 seeds and 14mL of CTAB (3mol / L) at 40°C for 1h to obtain solution 5, and 0.35g of metal oxide ZrO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0167] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml of 1mol / L iron nitrate, cerium nitrate, lanthanum nitrate mixed solution (iron-cerium-lanthanum molar ratio of 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-3. The content of active components is 0.1% by weight, the particle size of active components is between 5-6nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 8-19.5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.2%.
[0168] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 325℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 300h (i.e., the reaction was carried out continuously for 300h, and the catalytic activity of the catalyst did not decrease significantly).
[0169] Example 4
[0170] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0171] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 30mL of CTAB (3mol / L) at 40°C for 1h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0172] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-4. The content of active components is 0.1% by weight, the particle size of active components is between 2-3nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 8-19.5nm, and the specific surface area is about 500m 2 / g, and the powder loss rate of the coating is 0.2%.
[0173] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 225℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0174] Example 5
[0175] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0176] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 14mL of CTAB (3mol / L) at 40°C for 1h to obtain solution 5, and 1g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0177] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-5. The content of active components is 0.1% by weight, the particle size of active components is between 3-4nm; the particle size of coating is between 100-200nm, the mesopore size distribution is 8-19.5nm, and the specific surface area is about 400m 2 / g, and the powder loss rate of the coating is 0.5%.
[0178] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 150h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0179] Example 6
[0180] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0181] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 14mL of CTAB (3mol / L) at 40°C for 1h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 10h to obtain coating slurry 6.
[0182] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-6. The content of active components is 0.1% by weight, the particle size of active components is between 2-3nm, the particle size of coating is between 50-100nm, the mesopore size distribution is 8-19.5nm, and the specific surface area is about 550m 2 / g, and the powder loss rate of the coating is 0.05%.
[0183] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 215℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0184] Example 7
[0185] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0186] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 14mL of CTAB (3mol / L) at 25°C for 1h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0187] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-7. The content of active components is 0.1% by weight, the particle size of active components is between 2-3nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 6-12nm, and the specific surface area is about 550m 2 / g, and the powder loss rate of the coating is 0.1%.
[0188] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1, reaction pressure 0.1MPa, reaction temperature 215℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0189] Example 8
[0190] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0191] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 30mL of CTAB (3mol / L) at 40°C for 10h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0192] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml of 1mol / L iron nitrate, cerium nitrate, lanthanum nitrate mixed solution (iron-cerium-lanthanum molar ratio of 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-8. The content of active components is 0.1% by weight, the particle size of active components is between 2-3nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 5-10nm, and the specific surface area is about 600m 2 / g, and the powder loss rate of the coating is 0.1%.
[0193] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 195℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0194] Example 9
[0195] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0196] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 3.5g of commercially available ZSM-5 seeds and 14mL of CTAB (3mol / L) at 100°C for 1h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0197] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-9. The content of active components is 0.1% by weight, the particle size of active components is between 2-3nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 5-8.5nm, and the specific surface area is about 600m 2 / g, and the powder loss rate of the coating is 0.1%.
[0198] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 195℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0199] Example 10
[0200] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0201] Secondly, 5g of ethanol was mixed with 0.568g of sodium aluminate to obtain solution 1. 27.9g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58g of ethyl orthosilicate and 6.9g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. Transparent gel liquid 4 was mixed and stirred with 0.5g of commercially available ZSM-5 seeds and 30mL of CTAB (3mol / L) at 40°C for 1h to obtain solution 5, and 0.35g of metal oxide TiO2 was added to solution 5, mixed and ball-milled for 2h to obtain coating slurry 6.
[0202] Then, 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (molar ratio of iron to cerium to lanthanum is 1:1:1) were stirred at 25°C and pH 9 for 3h to obtain solution 7. Solution 7 was added to coating slurry 6 and stirred for 30min to obtain mixed slurry 8, and then mixed slurry 8 was added dropwise to the acid-treated cordierite honeycomb ceramic, purged with a 2MPa air knife, treated in a 100°C drying oven for 12 hours, and calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain catalytic oxidation catalyst Cat-10. The content of active components is 0.1% by weight, the particle size of active components is between 5-6nm, the particle size of coating is between 80-150nm, the mesopore size distribution is 20-25nm, and the specific surface area is about 300m 2 / g, and the powder loss rate of the coating is 0.3%.
[0203] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 305℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 250h (i.e., the reaction was carried out continuously for 250h, and the catalytic activity of the catalyst did not decrease significantly).
[0204] Comparative Example 1
[0205] The catalytic oxidation catalyst prepared according to the method of Example 1 is different in that the cordierite honeycomb ceramic is not subjected to acid treatment, and the coating slurry is directly added to the cordierite honeycomb ceramic that has not been treated with acid, thereby preparing a monolithic catalyst Cat-D1, wherein the content of the active component is 0.1% by weight, the particle size of the active noble component is between 5 and 6 nm, the particle size of the coating is between 100 and 200 nm, the mesopore size distribution is 10-45 nm, and the specific surface area is about 300 m 2 / g, and the powder loss rate of the coating is 5%.
[0206] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1, reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO concentration was about 1000ppm, VOCs concentration was about 5000ppm, conversion rate was 50%, and catalyst stability was 10h.
[0207] Comparative Example 2
[0208] Based on Example 1, the difference is that the coating slurry is prepared according to the following process:
[0209] 50g of ZSM-5 molecular sieve (purchased from Nankai Catalyst Company, brand NKF-5) was mixed with 100g of deionized water, and wet ball milling was used to obtain a molecular sieve slurry. 0.5L of 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml of 1mol / L ferric nitrate, cerium nitrate, lanthanum nitrate mixed solution (iron-cerium-lanthanum molar ratio of 1:1:1) were taken and stirred for 3h at 25°C and pH 9 to obtain a mixed solution. The mixed solution was added to the molecular sieve slurry and stirred for 30min to obtain a coating slurry. Then, the coating slurry was added dropwise to the acid-treated cordierite honeycomb ceramic, and purged, dried, calcined, and reduced in sequence to obtain a monolithic catalyst Cat-D2. Among them, the content of active components is 0.1% by weight, the particle size of active noble components is between 5-10nm, the particle size of coating is between 500-600nm, the mesopore size distribution is 0nm, and the specific surface area is about 100m 2 / g, and the powder loss rate of the coating is 0.1%.
[0210] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO concentration was about 500ppm, VOCs concentration was about 1000ppm, conversion rate was 90%, and catalyst stability was 1h.
[0211] It can be seen from the above examples and comparative examples that the catalytic oxidation catalyst prepared by the present invention exhibits a good catalytic effect in the process of catalytic oxidation removal of carbon-based oxygen-containing molecular gases, and the catalyst stability is significantly better, and is suitable for continuous long-term operation.
[0212] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalytic oxidation catalyst, characterized in that: The catalytic oxidation catalyst comprises: A carrier, wherein the carrier is a regular carrier treated with acid; a coating layer attached to the support, the coating layer comprising a ZSM-5 molecular sieve and optionally a metal oxide; and an active component dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal; The particle size of the coating is 50-500nm, the mesopore size is 3-50nm, and the specific surface area is 300-600m 2 / g, and the particle size of the active component is 1-8nm.
2. The catalytic oxidation catalyst according to claim 1, characterized in that The particle size of the coating is 80-300nm, the mesopore size is 4-30nm, and the specific surface area is 350-500m 2 / g, and the particle size of the active component is 2-6nm.
3. The catalytic oxidation catalyst according to claim 1 or 2, characterized in that: The powder loss rate of the coating is below 1%, preferably 0.1-1%.
4. The catalytic oxidation catalyst according to any one of claims 1 to 3, characterized in that: Relative to 100 parts by weight of the carrier, the content of the coating layer is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight.
5. The catalytic oxidation catalyst according to any one of claims 1 to 4, characterized in that: The structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
6. The catalytic oxidation catalyst according to any one of claims 1 to 4, characterized in that: In the coating, the weight ratio of the ZSM-5 molecular sieve to the metal oxide is 1:0.1-0.
5.
7. The catalytic oxidation catalyst according to claim 1 or 6, characterized in that: In the coating, the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
8. The catalytic oxidation catalyst according to any one of claims 1 to 4, characterized in that: In the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.
3.
9. The catalytic oxidation catalyst according to claim 1 or 8, characterized in that: The noble metal is selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium.
10. The catalytic oxidation catalyst according to claim 1 or 8, characterized in that: The alloy metal is at least one of Fe, La and Ce, and is preferably a combination of Fe, La and Ce.
11. A method for preparing a catalytic oxidation catalyst, characterized in that: The method comprises the following steps: (1) treating the structured support with acid; (2) mixing an alcohol solution of sodium metaaluminate with an aqueous solution containing a microporous template and a silicon source, aging, removing alcohol, and then mixing the obtained gel solution with ZSM-5 molecular sieve seed crystals and a mesoporous template; (3) mixing the mixed solution obtained in step (2) with the metal oxide and ball milling to obtain a coating slurry; (4) The coating slurry is mixed with a mixed solution containing a noble metal precursor and a structural additive, and the obtained mixed slurry is added to the structured support treated with acid, and then purged, dried, calcined and reduced in sequence.
12. The method according to claim 11, characterized in that In step (1), the acid treatment process includes: using an acidic solution to reflux the structured carrier, then washing it to neutrality and drying it; Preferably, the concentration of the acidic solution is 1-3 mol / L; Preferably, the acid in the acidic solution is at least one of nitric acid, sulfuric acid and hydrochloric acid; Preferably, the conditions of the reflux treatment include: a temperature of 70-90° C. and a time of 12-36 hours; Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
13. The method according to claim 11, characterized in that In step (2), the specific process of mixing the alcohol solution of sodium metaaluminate with the aqueous solution containing the microporous template and the silicon source is as follows: adding the alcohol solution of sodium metaaluminate to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours; Preferably, the microporous template is selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide; Preferably, the silicon source is selected from at least one of silicate, silicic acid, silica hydrogel and tetraethyl orthosilicate; Preferably, the concentration of the mesoporous template agent is 0.5-5 mol / L, preferably 1-3 mol / L; Preferably, the mesoporous template agent is hexadecyltrimethylammonium bromide.
14. The method according to claim 11, characterized in that In step (3), the metal oxide is selected from at least one of TiO2, Al2O3, La2O3, CeO2, MgO and ZrO2.
15. The method according to claim 11, characterized in that In step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12; Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, hexahydroxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate; Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
16. The method according to claim 11, characterized in that In step (4), the purging process is performed by using an air knife purging at 1.5-2.5 MPa; Preferably, the calcination conditions include: a temperature of 200-300° C. and a time of 4-10 hours; Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations; Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
17. A catalytic oxidation catalyst prepared by the method according to any one of claims 11 to 16.
18. Use of the catalytic oxidation catalyst according to any one of claims 1 to 10 and 17 in removing carbon-based oxygen-containing molecular gases from exhaust gas.
Citation Information
Patent Citations
Honeycomb-ceramic-type monolithic catalyst, and preparation method and application thereof
CN102133537A
Precious metal monolithic catalyst for organic waste gas treatment and manufacturing method thereof
CN102366723A
Oxidation catalyst for purifying diesel engine waste gas and preparation method of oxidation catalyst
CN103071524A
Diesel vehicle oxidation catalyst containing Al-Si-Ti composite oxide
CN104117381A
Preparation method of honeycomb ZSM-5-based coating catalyst
CN113134385A